2020
DOI: 10.3390/cells9092093
|View full text |Cite
|
Sign up to set email alerts
|

Dim Light at Night Induced Neurodegeneration and Ameliorative Effect of Curcumin

Abstract: It is a well-known fact that following a proper routine light/dark or diurnal rhythm controls almost all biological processes. With the introduction of modern lighting and artificial illumination systems, continuous exposure to light at night may lead to the disruption of diurnal rhythm. However, the effect of light during the night on brain anatomy, physiology, and human body functions is less explored and poorly understood. In this study, we have evaluated the effect of exposure to dim light (5 lux) at night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 73 publications
4
19
0
Order By: Relevance
“…However, the administration of curcumin (150mg/kg) had effectively restored some of the anxiety-like behaviors including the percentage freezing time and frequency of grooming in mice. Corroborating this finding, in our previous study, we observed that the administration of curcumin in the Cd-induced neurotoxic mice model and normal light/dark-exposed mice revealed increased locomotor activity, reduced stress and anxiety-like behavior, and improved spatial learning and retention memory through the promotion of hippocampal neurogenesis [ 21 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…However, the administration of curcumin (150mg/kg) had effectively restored some of the anxiety-like behaviors including the percentage freezing time and frequency of grooming in mice. Corroborating this finding, in our previous study, we observed that the administration of curcumin in the Cd-induced neurotoxic mice model and normal light/dark-exposed mice revealed increased locomotor activity, reduced stress and anxiety-like behavior, and improved spatial learning and retention memory through the promotion of hippocampal neurogenesis [ 21 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 61%
“…Animals’ physiological processes are tuned to the external light/dark cycle of their surroundings. The effects of night-time light and constant darkness on the brain and behavior of laboratory animals are recent findings [ 21 ]. Recent studies show that chronic exposure to artificial light during the night elevates the chances of developing behavioral impairment in laboratory animals, such as sleep disturbance [ 34 , 35 ], mood fluctuation [ 36 ], and metabolic disorders [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-34a targets E2F3, Numbl, platelet-derived growth factor receptor A (PDGFRA), synaptotagmin 1 (Syt1), autophagy-related 9a (Atg9a), CD44, cyclic AMP response-element binding protein (CREB), brain-derived neurotrophic factor (BDNF) to inhibit cell proliferation, migration, invasion and adhesion [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. It regulates extracellular signal-regulated kinase 1/2 (ERK) and p38, and increases nuclear factor kappa light chain enhancer of activated B cells (NF-κB), Sirtuin 1 (SIRT1) and Bcl2, to promote or reduce apoptosis [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%